2010
DOI: 10.1001/archinternmed.2010.30
|View full text |Cite
|
Sign up to set email alerts
|

Implantable Cardiac Device Procedures in Older Patients

Abstract: Despite the fact that most device trials have excluded patients 80 years or older, more than one-fifth of ICD and CRT devices are implanted in this age group. Advanced age is an independent predictor of in-hospital mortality following device implantation, suggesting that additional study is needed to define criteria for appropriate device use in older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
4
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 35 publications
5
54
4
1
Order By: Relevance
“…12,13,25 However, a recent study including 26 887 recipients of ICD or CRT devices has shown a significant higher frequency of acute device-related adverse event among elderly patients, women, and black race/ethnicity. 26 Similar to the results of the InSync, MADIT-CRT, MIR-ACLE, and MIRACLE-ICD studies, the present evaluation showed that the rates of early adverse events were not different between young and elderly patients. About the long-term CRT-related complications, the data are scarce.…”
supporting
confidence: 88%
“…12,13,25 However, a recent study including 26 887 recipients of ICD or CRT devices has shown a significant higher frequency of acute device-related adverse event among elderly patients, women, and black race/ethnicity. 26 Similar to the results of the InSync, MADIT-CRT, MIR-ACLE, and MIRACLE-ICD studies, the present evaluation showed that the rates of early adverse events were not different between young and elderly patients. About the long-term CRT-related complications, the data are scarce.…”
supporting
confidence: 88%
“…A potential explanation is that concomitant comorbid conditions often seen in elderly patients may also affect survival. Swindle et al pointed out that advanced age and elevated comorbidity score were independent predictors of in-hospital mortality after CRT or implantable cardioverter-defibrillator placement (27). Older patients may also have higher risk of noncardiac death; however, we did not differentiate the cause of death after CRT.…”
Section: Discussionmentioning
confidence: 73%
“…29 There is, however, no consistent evidence supporting a similar benefit of ICD treatment among younger and elderly patients. [30][31][32][33] This seems intuitive because older age is usually combined with more comorbid conditions that may dilute the salutary effects of ICD therapy. Advanced age was also found to constitute an independent predictor of in-hospital mortality following device implantation.…”
Section: Elderly Patientsmentioning
confidence: 99%